1986
DOI: 10.1002/jsfa.2740371108
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of safflower protein isolates: Water absorption, whipping and emulsifying characteristics

Abstract: Safflower meal defatted at the laboratory (SML) and safflower cake provided by an industrial plant (SMI) were used for protein isolation. Isolates were obtained by micellisation (MP) and isoelectric precipitation (IP) techniques. The functional properties studied with these isolates were water and fat absorption, foam expansion and stability, and emulsion activity and stability. Within the experimental conditions of this research, it was observed that the various treatments received previously by the safflower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 18 publications
2
9
2
Order By: Relevance
“…According to Mwasaru et al [21] differences in the emulsifying activity of protein may be related to their solubility and conformational stability. Paredes-Lopez et al [22] observed that the sample with the lowest solubility exhibited the lowest emulsifying activity and the highest emulsion stability, an observation partly consistent with the results obtained in the present study sinceHTC bean (P. vulgaris) protein concentrate at pH 5-6 exhibited the lowest solubility and the lowest emulsifying activity but was not the highest in emulsion stability. According to Mwasaru et al [21], hydrophobicity of proteins has also been reported to influence their emulsifying properties The results obtained here may partially result of the high hydrophobic amino acids content in the HTC bean (P. vulgaris) protein concentrate, which allows the protein-protein interaction in the interface.…”
Section: Functional Properties Of Hard-to-cook Bean (P Vulgaris) Prosupporting
confidence: 92%
“…According to Mwasaru et al [21] differences in the emulsifying activity of protein may be related to their solubility and conformational stability. Paredes-Lopez et al [22] observed that the sample with the lowest solubility exhibited the lowest emulsifying activity and the highest emulsion stability, an observation partly consistent with the results obtained in the present study sinceHTC bean (P. vulgaris) protein concentrate at pH 5-6 exhibited the lowest solubility and the lowest emulsifying activity but was not the highest in emulsion stability. According to Mwasaru et al [21], hydrophobicity of proteins has also been reported to influence their emulsifying properties The results obtained here may partially result of the high hydrophobic amino acids content in the HTC bean (P. vulgaris) protein concentrate, which allows the protein-protein interaction in the interface.…”
Section: Functional Properties Of Hard-to-cook Bean (P Vulgaris) Prosupporting
confidence: 92%
“…In comparison to the RCNI, the foaming capacity of HCNI was superior at pH 7 and 8. The foaming capacity profile of the RCNI was similar to that of lupin [27], safflower [24] and groundnuts [4] proteins. Apparently, low foaming capacity of these isolates at their isoelectric pH could be attributed to their low solubility.…”
Section: Resultsmentioning
confidence: 86%
“…Water absorption capacity was determined according to ParedesLopez and Ordorica-Falomir [14], using a filter funnel connected with a capillary tube filled with water. Oil (sunflower oil) absorption capacity was measured using a known volume of oil added to 1 g of protein sample and free oil was measured and oil adsorbed is expressed as ml of oil retained (bound) per g protein.…”
Section: Functional Propertiesmentioning
confidence: 99%